2014
DOI: 10.1038/jid.2013.340
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor/microRNA Axis Blocks Melanoma Invasion Program by miR-211 Targeting NUAK1

Abstract: Melanoma is one of the deadliest human cancers, responsible for approximately 80% of skin cancer mortalities. The aggressiveness of melanoma is due to its capacity to proliferate and rapidly invade surrounding tissues, leading to metastases. A recent model suggests melanoma progresses by reversibly switching between proliferation and invasion transcriptional signatures. Recent studies show that cancer cells are more sensitive to microRNA (miRNA) perturbation than are non-cancer cells; however, the roles of miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
131
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(140 citation statements)
references
References 66 publications
7
131
0
2
Order By: Relevance
“…Recently, abundant studies have already reported the importance of miRNAs in an increasing number of cancers [5,6]. In melanoma, some miRNAs have been found abnormally expressed, such as miR-153-3p [7], miR-211 [8], miR-196a [9], miR-30b, and miR-30d [10]. They have been revealed as oncogenes or tumor suppressor genes in melanoma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, abundant studies have already reported the importance of miRNAs in an increasing number of cancers [5,6]. In melanoma, some miRNAs have been found abnormally expressed, such as miR-153-3p [7], miR-211 [8], miR-196a [9], miR-30b, and miR-30d [10]. They have been revealed as oncogenes or tumor suppressor genes in melanoma.…”
Section: Introductionmentioning
confidence: 99%
“…They have been revealed as oncogenes or tumor suppressor genes in melanoma. For instance, ectopic expression of miR-211 in melanoma cell lines resulted in significant inhibition of growth and invasion compared to parental cells [8]. Contrary to miR-211, miR-30b and miR-30d were reported to have functions as potential tumor promoters, as evidenced by simultaneously promoting cellular invasion and immunosuppression in melanoma cells [10].…”
Section: Introductionmentioning
confidence: 99%
“…Like many well-defined miRNAs, the diverse target genes of miR-211 have been identified and characterized, including PP2Cm [18], Cyclin D1, CDK6 [27], SATB2 [28], CDC25B [29], NUAK1 [30], TGFβR II [31], CHD5 [32] and BRN2 [33]. Based on our preliminary finding, we employed the miRanda algorithm [19] to analyze the potential regulatory effect of miR-211-5p on IL-10.…”
Section: Discussionmentioning
confidence: 99%
“…miR-211 has several putative target genes, including the calcium-activated potassium channel subunit ␣-1 gene (KCNMA1), the insulin-like growth factor 2 receptor gene (IGF2R), the transforming growth factor ␤ receptor 2 gene (TGFBR2), the insulin growth factor binding protein 5 gene (IGFBP5), the POU domain-containing transcription factor gene BRN2, the nuclear factor of activated T cells 5 gene (NFAT5), and NAUK1 (10,13,17,18).…”
mentioning
confidence: 99%